1995
DOI: 10.1128/aem.61.4.1599-1609.1995
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenetic analyses of Bradyrhizobium strains nodulating peanut (Arachis hypogaea L.) roots

Abstract: Seventeen Bradyrhizobium sp. strains and one Azorhizobium strain were compared on the basis of five genetic and phenetic features: (i) partial sequence analyses of the 16S rRNA gene (rDNA), (ii) randomly amplified DNA polymorphisms (RAPD) using three oligonucleotide primers, (iii) total cellular protein profiles, (iv) utilization of 21 aliphatic and 22 aromatic substrates, and (v) intrinsic resistances to seven antibiotics. Partial 16S rDNA analysis revealed the presence of only two rDNA homology (i.e., identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 51 publications
7
35
0
5
Order By: Relevance
“…The nodulation ability of all isolates was confirmed by the formation of typically reddish nodules. The isolation of fast-growing rhizobia from peanut nodules is worth [3,4,14,15]. Our findings reveal peanut as a broad-range host and coincide with recent work by Taurian et al [5,16] which reported efficient native populations of fast-growing rhizobia associated to this species in central Argentina.…”
Section: Resultssupporting
confidence: 90%
“…The nodulation ability of all isolates was confirmed by the formation of typically reddish nodules. The isolation of fast-growing rhizobia from peanut nodules is worth [3,4,14,15]. Our findings reveal peanut as a broad-range host and coincide with recent work by Taurian et al [5,16] which reported efficient native populations of fast-growing rhizobia associated to this species in central Argentina.…”
Section: Resultssupporting
confidence: 90%
“…SDS-PAGE of total proteins can often reveal genetic variation within a species, but does not give reliable information on more distant genetic relationships (de Lajudie et al 1994;Dupuy et al 1994;Van Rossum et al 1995). In our study, isolates with the same 16S rRNA partial sequence often had quite dissimilar SDS-PAGE patterns, while strains with the same SDS-PAGE pattern belonged to the same or closely related 16S groups (Table 1).…”
Section: Discussionmentioning
confidence: 60%
“…These results may indicate that the tolerance of strains to antibiotics and heavy metals is not correlated with their growth rate, but it could also be related to the bacterial species. Stowers (1985) and van Rossum et al 1995) reported that fast-growing rhizobia could metabolize a wider range of Nour et al (1994aNour et al ( , 1994b, showed that chickpea rhizobia strains from Morocco (more than 90% of them being very slow growers), could utilize a broad range of carbohydrates. On the other hand, some carbon sources such as b-methyl-xyloside and amethyl-glucoside were exclusively metabolized by some stains of cluster III and cluster I, respectively.…”
Section: Discussionmentioning
confidence: 99%